Tariff-Tax Reforms and Market Access - Udo Kreickemeier; Pascalis Raimondos-Møller (Copenhagen Business School (CBS), Department of Economics, 2006)
Reducing tariffs and increasing consumption taxes is a standard IMF advice to countries that want to open up their economy without hurting government finances. Indeed, theoretical analysis of such a tariff-tax reform shows an unambiguous increase in welfare and government revenues. The present paper examines whether the country that implements such a reform ends up opening up its markets to international trade, i.e. whether its market access improves. It is shown that this is not necessarily so. We also show that, comparing to the reform of only tariffs, the tariff-tax reform is a less efficient proposal to follow both as far as it concerns market access and welfare.
hdl:10398/7629
Keywords: F13; H20; 330; market access; tariff reform; consumption tax reform